Neue Entwicklungen in der Therapie des fortgeschrittenen klassischen Hodgkin-Lymphoms - Kreissl, Stefanie; Eichenauer, Dennis Alexander; Meißner, Julia; Topp, Max S.; Engert, Andreas; Borchmann, Peter (Der Onkologe, 2018)
BackgroundWith the current standard of care of the German Hodgkin Study Group (DHSG) consisting of interim positron emission tomography (PET)-guided administration of 4-6 cycles of BEACOPPescalated (escalated-dose bleomycin, etoposide, doxorubicin, cyclophosphamide, vincristine, procarbazine, prednisone) plus radiotherapy of PET-positive residual lymphoma, the overall survival (OS) of patients with advanced Hodgkin’s lymphoma (HL) is in excess of 95%; however, further minimization of acute and delayed toxicities without compromising the tumor-specific outcome of patients is needed, as defining the right balance between efficacy and toxicity remains the most important challenge in HL.ObjectiveThe aim of this article is to provide an overview of the current standard of care and recent developments in the treatment of advanced HL.Material and methodsBy a systematic literature search, relevant publications as well as reports on new approaches that are being evaluated in current trials were collated and are summarized.ResultsRecent comparisons of BEACOPPescalated and ABVD (Doxorubicin, Bleomycin, Vinblastin, Dacarbazin) regimens showed a substantial benefit of BEACOPPescalated in terms of progression-free survival (PFS) and OS. The interim PET-guided administration of 4-6 cycles of BEACOPPescalated can be considered a safe, feasible and highly active approach. This strategy might be improved by the implementation of targeted drugs, such as brentuximab vedotin; therefore, standard BEACOPPescalated is currently randomly compared with a variant named Brentuximab Vedotin, etoposide, cyclophosphamide, doxorubicin, dacarbazine, dexamethasone (BrECADD), which was previously shown to be safe and feasible in a phase II study.ConclusionThe major goal in the treatment of advanced HL is the minimization of toxicity without compromising efficacy. Targeted drugs might replace unspecific cytotoxic drugs, which cause systemic toxicity. Hence, the antibody-drug conjugate brentuximab vedotin is currently being investigated as a component of the BEACOPP variant BrECADD in the randomized DHSG HD21 trial.